Design, fabrication, and analysis of a smart mower - Tan, Qing Foong; Siti Zubaidah, Ismail (Penerbit UMP, 2019)
This paper focusses on optimisation of vibration and sound levels of a lawnmower from process cutting with the cutting blade. Technical requirements have been defined for the project including customer requirement, cost model of the product, the checklist of product design specification, concept generation, concept selection and prototyping. These are the fundamental technical requirement to build a safe and efficient of Smart Mower. The experiment was analysed using 200 to 900 wedge angles of cutting blade to cutting grass field simulation for the test of levels of vibration and sound. From the results, it is observed that the analysis of changing wedge angle will provide changes on levels of vibration and sound. The obtained results indicate that the smaller wedge angle gives smaller levels of vibration and sound. The results can also significantly meet all customer requirement according to product development. Therefore, the wedge angle is promising the reduction of vibration level and sound level. At last, this result can reduce the cost, time to market and improve product reliability and customer confidence.